Digital economy development in Eastern Indonesia: The infrastructure and socio-economic dimensions - I Made Jyotisa Adi Dwipatna; Dirmansyah Darwin; Shadry Andriani; Putu Ananda Devi Nugraha; Andi Nur Wahyuningsih (Privietlab, 2025)
The growth of the digital economy brings both challenges and opportunities for regional economic development, especially in areas where infrastructure and human resources are unevenly distributed. This study examines how digital infrastructure and socio-economic factors influence ICT competence, which is a key driver of digital economic progress in Eastern Indonesia. Using data from 13 provinces between 2016 and 2023, the study applied a Fixed Effects Model (FEM) to analyze regional and time-based differences. The results show that Internet access has a strong positive impact on ICT competence, highlighting the critical role of digital infrastructure in boosting participation and reducing the digital gap. Education also plays a significant role, with improved education helping to build digital literacy and better prepare the population for technological change. On the other hand, income does not seem to have a significant effect on ICT competence, suggesting that economic factors are not yet the main drivers of technological skills in the region. Overall, the findings emphasize that digital development in Eastern Indonesia is primarily influenced by the availability of infrastructure and the quality of human resources. To support inclusive and sustainable digital growth, policies should focus on ensuring equal access to the Internet and incorporating digital literacy into education.